IMPLEMENTATION OF RELIGIOUS EDUCATION IN FORMING AN ATTITUDE OF RESPONSIBILITY OF STUDENTS IN LUQMAN MODERN ISLAMIC BOARDING SCHOOL, BANDAR TONGAH, SIMALUNGUN - M. Rizkoni Salis; Husaini Husaini (Sean Institute, 2022)
This study aims to determine the implementation of religious education in shaping the attitude of responsibility of the students of Luqman Bandar Tongah Simalungun Islamic Modern Islamic Boarding School. Qualitative method with descriptive analysis is used in this study, while this type of research approach is with case studies or field research that leads to data collection in the field. Collecting data using observation and interview techniques. This research shows the results that the implementation of religious education in shaping the attitude of responsibility of students includes: cleaning and maintaining the cleanliness of the environment, saving at the cooperative every month, using the official language (Arabic and English), becoming administrators of the student organization, participating in Muhadhoroh (Speech Practice in 3 languages), deposit Tahfidz (memorization) of the Qur'an, following self-defense, and scouting.